Analysis of The Influence of Green Accounting, Company Size, and Dividend Payout Ratio on Profitability - Windi Ar, Baiq Melati Sepsa; Handajani, Lilik; Nurabiah, N. (Golden Ratio of Finance Management, 2025)
This research aims to determine the effect of green accounting, company size, and dividend payout ratio on the profitability of manufacturing sector companies listed on the Indonesian Stock Exchange in 2017-2021. This research is associative research with a quantitative approach. This research uses secondary data from annual and sustainability reports on manufacturing sector companies listed on the Indonesia Stock Exchange during the observation period from 2017 to 2021. The population in this study is manufacturing sector companies listed on the Indonesian Stock Exchange. The sample used in this research was 30 sample companies obtained based on the purposive sampling method, so that the total number of observations was 150 company observations during the five years of research. Hypothesis testing uses multiple linear regression analysis. This research shows that green accounting and dividend payout ratio do not affect profitability. Meanwhile, company size influences profitability.